Advances in future manufacturing engineering proceedings of the 2014 International Conference on Future Manufacturing Engineering (ICFME 2014), Hong Kong, December 10-11, 2014 - Yang, Guohui (Studies in materials science and mechanical engineering, 2015)
The International Conference on Future Manufacturing Engineering (ICFME 2014) was held in Hong Kong, December 10-11, 2014. It gathered academics, industry managers and experts, manufacturing engineers, university students all interested or proficient in the field of manufacturing engineering, including research, design and development of systems, processes, machines, tools and equipment. The manufacturing engineer's primary focus is to turn raw materials into a new or updated product in the most economic, efficient and effective way possible. This field also deals with the integration of different facilities and systems for producing quality products (with optimal expenditure) by applying the principles of physics and the results of manufacturing systems studies, such as Design and Manufacturing, Materials Science and Materials Processing Technology, Computer-aid Manufacturing, Mechanics